Light-induced transcription in zebrafish targets mitochondrial function and heme metabolism - Boiti, Alessandra; Weber, Hanna; Hong, Yuhang; Siauciunaite, Rima; Gornik, Sebastian G.; Foulkes, Nicholas S.; Vallone, Daniela (Antioxidants, 2025)
In fish cells, light exposure elevates levels of reactive oxygen species (ROS) and stress-activated MAP kinase activity and thereby induces gene transcription. However, we lack a complete understanding of the function and evolution of this regulatory mechanism. Here, we reveal that a set of mitochondrial and heme metabolism genes is transcriptionally induced in zebrafish cells upon exposure to light or elevated ROS. The integrity of D-box and E-box enhancers in these gene promoters is essential for their transcriptional activation. Furthermore, light-induced transcription of mitochondrial and heme metabolism genes is absent in a cell line derived from the blind Somalian cavefish (Phreatichthys andruzzii). This fish species has evolved in perpetual darkness and lacks light-dependent circadian and DNA repair responses as well as D-box-mediated and light- and ROS-induced transcription. PAR-bZip transcription factors bind to and activate transcription via the D-box. Cavefish homologs of these factors share extensive homology with their zebrafish counterparts and lack the deletion mutations that characterize other light-dependent genes in this species. These results extend the role of the D-box as a key regulator of light- and ROS-driven transcription in fish, beyond the circadian clock and DNA repair systems, to also encompass metabolic and mitochondrial function.